Peningkatan Safety Awareness Pada Kelompok UMKM Melalui Program Work Improvements in Small Enterprise (WISE) - Cattleya P.A. Islami, Mega; Dewi, Sinta; Novita Sari, Rizqi (EDUPEDIA Publisher, 2023)
Accidents and injuries are still 20% more common in small companies, including MSMEs, compared to large companies. Lack of safety awareness is one of the obstacles why safety is not widely implemented in the MSME area. In line with this description, the MSME group in Wiyung District, Surabaya City, has not experienced an increase in profit over the past few years, due to declining employee productivity. This is suspected because of the frequent occurrence of accidents that cause injuries to employees, thereby affecting their absenteeism levels and impacting lost working days which affects productivity. Based on these problems, training was carried out to increase safety awareness through the Work Improvements in Small Enterprise (WISE) program which aims to increase safety awareness for MSME groups as well as improve working conditions through the application of safety values.